Comparing the mental health and wellbeing of domestic and international tertiary students: A systematic review and meta-analysis - Xiong, Weiyang; Radunz, Marcela; Ali , Kathina; King, Daniel; Kyrios, Mike; Zhao, Yufang; Fassnacht, Daniel (Journal of International Students, 2024)
University study is a period of psychological vulnerability for many individuals, especially international students, due to challenges of relocation and acculturation. The aim of this meta-analytic review was to synthesize the literature on the mental health outcomes of domestic and international tertiary students. A total of 35 studies were identified via searching four databases. Results showed that among 283,412 participants, very small but non-significant effects were found between domestic and international students on anxiety. Among high-quality studies, international students reported fewer symptoms of anxiety, depression, and stress than domestic students. On the other hand, domestic students declared higher wellbeing scores. Despite these mixed findings, many students in the included studies reported poor mental health and wellbeing. Further research examining the mental health and wellbeing of domestic and international students is needed, with particular attention to the underlying needs and stressors that affect each subgroup to develop effective supports and countermeasures.